Known, absent and potential mineral deposit types in Australia. Issue 1 (1st December 2019) - Groves, David I.; Phillips, G. Neil
Summary: Australia is in the top six global producers for a wide range of mineral commodities of abundant metals (Fe, Mn, Al, Ti), base metals (Ni, Cu, Zn, Pb), precious metals (Au, Ag), scarce metals (REE, Li, Sb), energy metals (U, Th) and industrial/ precious minerals (salt, diamonds, zircon). Australia also has a wide range of uranium deposit types but their future is controlled by government policy. There are very few mineral deposit types that are not present or minor in the Australian continent. These include PGE deposits in large layered intrusions and Witwatersrand-type gold deposits, Carlin-type gold deposits, low-sulfidation-type epithermal Au-Ag deposits, Zambian-type copper deposits and MVT deposits. For most of these, appropriate depositional environments are extremely rare or absent. The future of the Australian mineral industry will continue to depend on a combination of brownfield exploration in known mineral districts and greenfields exploration, increasingly under deeper cover, for deposit classes within these mineral districts. Craton margins that are intruded by basic and/or felsic magmas are particularly attractive tectonic targets. They will continue to be fertile exploration environments for IOCG deposits and intrusion-hosted Ni-Cu deposits, and submarine gold-rich porphyry-to-VMS systems may have been neglected as exploration targets in the past. The future potential for pegmatite-hosted lithium deposits is high.